Sleep-Disordered Breathing and Symptoms of ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The frequency of sleep-disordered breathing (SDB) among children with inattention and hyperactivity was determined in 866 patients, aged 2.0 to 13.9 years (mean; 6.8 yrs), evaluated in two general pediatric clinics at the University of Michigan and University of Pittsburg.